2014
DOI: 10.5897/ajb2013.13320
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous leafy vegetables (imifino, morogo, muhuro) in South Africa: A rich and unexplored source of nutrients and antioxidants

Abstract: South Africa is endowed with agro-biodiversity that consists of different types of indigenous leafy vegetables (ILVs) with health benefits and rich source of nutrients to cater for over three million people suffering from hunger and malnutrition in the country. Unfortunately, the use of these vegetables is declining at an alarming rate due to negligence and lack of appropriate cultivation practices to improve yield, quality and adaptability of valuable species. The nutritional value and antioxidant potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
4
27
0
Order By: Relevance
“…More than 70% of freshwater bodies in urban areas are irreplaceably used for vegetable activity that has served as a means of livelihood among small scale farmers in most developing countries [2].Urban vegetable cultivation fuelled by the increased awareness, positive perception and consumption of "organic vegetables" [3], and the increasing demand of the export markets for vegetables, particularly West African countries [4,5] concerns in respect of the potential health risk of vegetables from these urban farms, principally those that use water from streams and lakes associated with human activity. Our earlier study (at the same location) had reported data in respect of the microbial safety (bacterial quality) of these vegetables and the water from a lake used for their irrigation following with a preventative approach supported by the FAO [9], particularly to avert the Toxic metals, essential elements,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 70% of freshwater bodies in urban areas are irreplaceably used for vegetable activity that has served as a means of livelihood among small scale farmers in most developing countries [2].Urban vegetable cultivation fuelled by the increased awareness, positive perception and consumption of "organic vegetables" [3], and the increasing demand of the export markets for vegetables, particularly West African countries [4,5] concerns in respect of the potential health risk of vegetables from these urban farms, principally those that use water from streams and lakes associated with human activity. Our earlier study (at the same location) had reported data in respect of the microbial safety (bacterial quality) of these vegetables and the water from a lake used for their irrigation following with a preventative approach supported by the FAO [9], particularly to avert the Toxic metals, essential elements,…”
Section: Introductionmentioning
confidence: 99%
“…More than 70% of freshwater bodies in urban areas for vegetable growing [1], an as a means of livelihood among small scale farmers in most developing .Urban vegetable cultivation has been ed by the increased awareness, positive and consumption of "organic , and the increasing demand of the tables, particularly among [4,5]. However, there are concerns in respect of the potential health risk of vegetables from these urban farms, principally those use water from streams and lakes associated with human activity.…”
Section: Introductionmentioning
confidence: 99%
“…African leafy vegetables (ALVs) have been recognised as essential contributors of a balanced diet [3] as well as functional foods as they provide health beyond the basic nutritional requirements [4]. As such Cleome gynandra (spider plant) is an African green leafy vegetable that is consumed in various African countries such as Botswana [5], Ghana [6], Kenya [7], Namibia [8], South Africa [4], Tanzania [9] and Zimbabwe [10]. It has been utilised traditionally to treat stomach aches, headaches [11], ear diseases [12], food poisoning, rheumatism, sexual asthenia, antibacterial infections and snake bites [13].…”
Section: Introductionmentioning
confidence: 99%
“…Chenopodium album and Solanum nigrum are functional food-plants with wide nutritional and medicinal importance among rural communities in the O.R. Tambo District Municipality of South Africa [11]. They are jointly referred to as imifino ezikhulelayo in isiXhosa, meaning indigenous vegetable.…”
Section: Introductionmentioning
confidence: 99%